An Open Labelled, Parallel Arm Interventional Clinical Assessment of Vasa (Justicia Adhatoda L.) in Dadru Kushtha (Fungal Skin Infection) - Harsh Upadhyay; Suman Singh; Neha Parmar; Dilip Jani (International Journal of Ayurveda and Pharma Research, 2021)
Vasa is a prime drug of respiratory disorders in Ayurveda. Seers of Ayurveda have also prescribed it as a single drug in Kushtha Roga in various dosage forms. It possesses Tikta Rasa Pradhana–Kashaya Anurasa, Sheeta Virya, Laghu Guna and Kapha-Pitta Hara properties. Many experimental studies like antitussive, bronchodilator activity, anti-asthmatic activities and clinical study were conducted to evaluate its Kasahara, Shwasahara, Raktapittahara Karma. But till date not a single study conducted to evaluate its Kushthaghna effect. Hence, an attempt was made to clinically compare Vasa with standard drug Nimba for its Kushthghna Karma. Aim: To clinically assess the effect of Vasa in Dadru Kushtha. Settings and Design: Interventional, Open labeled, Randomized, Parallel arm. Methods and Material: Fresh leaves of Vasa were collected from periphery of Rajpipla, Gujarat. The patients were selected from Government Ayurved College & Hospital, Vadodara and grading analogue scale, general & physical examination was done as a screening. Statistical analysis used: Data were calculated by student ‘t’ test for parametric data using Sigma stat 3.2. Results: Vasa showed statistically significant (p<0.001) results in all symptoms of Dadru Kushtha. Group A- (Nimba) showed 75.83% and Group B- (Vasa) showed 78.54% improvement in all symptoms of Dadru. The chief complaint of Dadru Kushtha i.e., Kandu was better relieved by Vasa on the basis of percentage of relief i.e. 97.92% in comparison to Nimba i.e., 89.58. Conclusion: Vasa is effective in all the symptoms of Dadru Kushtha. Current study suggests that it can be effectively used in Kapha pitta pradhana Kushtharoga.